FORMATION OF ORAL SPEECH SKILLS IN FUTURE PRIMARY LANGUAGE TEACHERS OF PRIMARY SCHOOL IN ENGLISH LANGUAGE CLASSES - Martyn, Natalia (Mountain School of Ukrainian Carpaty, 2021)
Today, the content of teaching foreign languages in secondary schools of Ukraine is being significantly updated, which is primarily due to the implementation of the Concept of the New Ukrainian School. Among the 10 key competences, the strategic educational document distinguishes communication in foreign languages. Thus, the formation of communicative skills of the future primary school teacher in the system of higher education is one of the priority tasks. The aim of the article is to substantiate the communicative aspect of the formation of oral skills, training of future primary school teacher of English as a component of his language competence. The content of English language teaching of students is based on the following main characteristics: it corresponds to the actual communicative and cognitive interests of future teachers of English, reflects the real needs of the use of language as a means of communication, is as close as possible to the conditions and goals of real intercultural communication; stimulates the development of interests and positive attitude to the English language, influences their motivational sphere; based on the experience of mastering the native language; takes into account the general educational experience of students which has been acquired during the mastering of the school foreign language course, as well as other subjects(interdisciplinary links); stimulates students’ independent activity, encourages reflection on the quality of their own academic achievements and the desire to improve them. In order to develop the skills of oral speech(speaking) in future teachers of English, the teacher, first of all needs to create preconditions for the organization of an active educational process, to prepare the appropriate educational and didactic base, to choose the optimal educational and methodological materials etc. It will be appropriate to use innovative educational technologies, for example, the use of video materials, which will significantly intensify the learning process, to increase the level of language competence of future teachers of English, to expand the range of use of methodological tools in teaching.